Solanum betaceum Extract as a Protective on Spermatozoa Morphology of Mice Exposed to Lead Acetate - Rima Wirenviona; Reny I'tishom; Siti Khaerunnisa; Anak Agung Istri Dalem Cinthya Riris; Nurul Fatimah Susanti; Nurul Jannatul Wahidah; Abadiyah Zakiah Kustantina (Universitas Muhammadiyah Surabaya, 2021)
Environmental pollution is one of the factors that contribute to the decline in male fertility. Lead is one of six air pollutants harmful to the reproductive system. One parameter of infertility in men is an increase in reproductive function observed with decreased morphological abnormalities of spermatozoa. The purpose is to analyze the effect of giving various dosages of Solanum betaceum extract on spermatozoa morphology of mice exposed to lead acetate. This study was true experimental using a randomized post-test only control group design. The total sample was 40 male mice Balb/ C taken by simple random sampling technique. Treatment and maintenance of experimental animals for 35 days. Statistical tests showed there were significant differences with p-value 0.005. Solanum betaceum extract can be used as a protective to improve the normal morphology spermatozoa of mice that exposed to lead acetate.